Increasing the Endurance of Futsal Athletes by Providing Green Bean Porridge - Syahruddin Syahruddin; Muhammad Syahrul Saleh; M. Sahib Saleh (UNIVERSITAS NEGERI MAKASSAR, 2024)
This research aims to find out whether there is an increase in the endurance of futsal athletes through feeding green bean porridge. Experimental type of research. Experimental research is research that seeks to find the influence of certain variables on other variables under strictly controlled conditions. So the population of this study was all futsal athletes at SMA Negeri 9 Makassar. A sample of 10 people was obtained based on the criteria, namely males aged 15-17 years using a purposive sampling technique. The data analysis techniques used are descriptive tests, normality tests, and T-tests (hypothesis tests) using a computer via SPSS 16.0 with a sig level of 0.05. Based on data analysis, the results of descriptive tests with the group given green bean porridge obtained an average value (mean) of 37.61 with a standard deviation of 2.99 a minimum value of 32.90, a maximum of 41.10. The group without giving green bean porridge obtained an average value (mean) of 34.64 with a standard deviation of 3.49 a minimum value of 29.50 and a maximum of 39.90. The results of the data normality test were with a total of Asymp= 0.99 (pretest) and with a total of Asymp= 0.65 (posttest) where the value of sig0.00 <0.05. Hypothesis test results (T-test) data between the pretest and post-test have a mean difference of 92.97) so it can be concluded that there is an increase in giving 100 grams of green bean porridge to vo2Max in futsal athletes at SMA Negeri 9 Makassar.